The Role of Strategic Patience in Enhancing Marketing Excellence Through the Marketing Lens - Sanaa Jasim Mohammed; Ali Aboudi Nehme; Zaid Abdulzahra Jaffar (Universitas Muhammadiyah Sidoarjo, 2025)
General Background This study addresses the growing need for organisations to adopt long-term strategic approaches capable of sustaining competitiveness in dynamic markets, where marketing excellence increasingly depends on deliberate decision-making and adaptive learning. Specific Background Within the retail apparel sector in Ziona Mall and Al-Harithiya, the concept of strategic patience has been recognised but insufficiently examined in relation to marketing excellence and the mediating role of the marketing lens. Knowledge Gap Despite its theoretical prominence, empirical evidence on how strategic patience is channelled through marketing perspectives to enhance marketing excellence remains limited. Aims This research investigates the direct effects of strategic patience on the marketing lens and marketing excellence, and evaluates the marketing lens as a mediating mechanism. Results Using data from 189 employees and structural equation modelling, the study reveals strong and significant effects of strategic patience on the marketing lens, a weaker yet significant direct effect on marketing excellence, and a robust indirect effect indicating partial mediation. Novelty The study demonstrates that strategic patience contributes to marketing excellence primarily through the marketing lens rather than through direct influence alone. Implications These findings highlight the need for apparel retailers to strengthen culture management, knowledge development, and stakeholder engagement so that strategic patience can translate into sustainable marketing performance.Highlight : The study underscores the strong link between strategic patience and the marketing lens, which serves as the primary mechanism for elevating marketing excellence. Findings show that stakeholder engagement remains the weakest dimension, indicating the need for more consistent external collaboration. Customer value emerges as the lowest-performing aspect, signalling that stores must clarify and strengthen the value delivered to customers Keywords : Strategic Patience, Marketing Excellence, Marketing Lens, Ziona Mall, Al-Harithiya